((x+3)2)+6x=46

Simple and best practice solution for ((x+3)2)+6x=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((x+3)2)+6x=46 equation:


Simplifying
((x + 3) * 2) + 6x = 46

Reorder the terms:
((3 + x) * 2) + 6x = 46

Reorder the terms for easier multiplication:
(2(3 + x)) + 6x = 46
((3 * 2 + x * 2)) + 6x = 46
((6 + 2x)) + 6x = 46
(6 + 2x) + 6x = 46

Remove parenthesis around (6 + 2x)
6 + 2x + 6x = 46

Combine like terms: 2x + 6x = 8x
6 + 8x = 46

Solving
6 + 8x = 46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 8x = 46 + -6

Combine like terms: 6 + -6 = 0
0 + 8x = 46 + -6
8x = 46 + -6

Combine like terms: 46 + -6 = 40
8x = 40

Divide each side by '8'.
x = 5

Simplifying
x = 5

See similar equations:

| 10x+9y=5z-8wforx | | 8s-8=8s-13+5 | | -5y+5x=3 | | -4y+5(-3)=17 | | -8y=-49 | | -236=4*4(8k-4) | | 11+X^2=47 | | AngleB=(2x-2) | | Tanx=9 | | 8.4x+y=9.0 | | Y-1=-3(x-0) | | 8x(-4y)=-4 | | X=2.25x | | 3xy+3xy=x | | Y=1/4(4)^3/2 | | 5(m-2)+36=t | | 13b-4=20+9b+20 | | -8p+14=22 | | 0=-5*y*y+10xy+50x | | 0.5abc-2ac= | | -6-1=x-21 | | -4m=21 | | 2x^2+2x-260=0 | | T-35=74 | | 6/144 | | 2(v-5)-4=-5(-3v+2)-3v | | 11.2x=556 | | 11+[-3c]-4c= | | 3/x-1/3=1/4 | | 9+1.2(7n-26)-8n= | | b-1.6/4=3 | | -3+x^2=50 |

Equations solver categories